2011
DOI: 10.1002/cncr.26063
|View full text |Cite
|
Sign up to set email alerts
|

Persistent disparities in liver transplantation for patients with hepatocellular carcinoma in the United States, 1998 through 2007

Abstract: BACKGROUND: Prior studies have demonstrated that among patients with hepatocellular carcinoma (HCC), African Americans (AAs) and Asian/Pacific Islanders (APIs) are substantially less likely to undergo liver transplantation (LT) compared with whites. The authors examined whether disparities in the receipt of LT among LT-eligible HCC patients changed over a 10-year time period, and whether the disparities might be explained by sociodemographic or clinical factors. METHODS: The National Cancer Data Base, a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…Our study, noted similar predictors of treatment, though we also examined the patient factors associated with receipt of non‐surgical therapies. This is also consistent with the body of literature describing racial and geographic disparities in cancer care and access across disease sites . Interestingly, in terms of payer status, patients with public insurance had a higher likelihood of treatment with non‐surgical therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study, noted similar predictors of treatment, though we also examined the patient factors associated with receipt of non‐surgical therapies. This is also consistent with the body of literature describing racial and geographic disparities in cancer care and access across disease sites . Interestingly, in terms of payer status, patients with public insurance had a higher likelihood of treatment with non‐surgical therapy.…”
Section: Discussionsupporting
confidence: 88%
“…This study also had no information on liver disease or hospital structural characteristics, and transcatheter arterial chemoembolization procedures were poorly captured . Other work has demonstrated disparities in liver transplantation in HCC . Our study, noted similar predictors of treatment, though we also examined the patient factors associated with receipt of non‐surgical therapies.…”
Section: Discussionmentioning
confidence: 80%
“…Several previous studies have identified possible explanations for this underutilization of surgical therapy. Some have suggested that demographic factors, such as race or socioeconomic status, influence the use of surgery for HCC . While socioeconomic factors may influence treatment, it is unclear if they affect survival .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, females have been reported to be disadvantaged in terms of overall liver transplant rates [6]. African Americans and Asian/Pacific Islanders are less likely to receive a liver transplant for HCC than White patients [7]. Differences in access to liver transplant have also been reported depending on insurance status, geography, and income status [810].…”
Section: Introductionmentioning
confidence: 99%